Experimental evaluation of out-of-plane capacity of masonry infill walls - André Furtado (2016)
Infill masonry (IM) walls are considered to be non-structural elements but, when subjected to earthquakes, they tend to interact with the surrounding RC (reinforced concrete) frames, which can result in different failure modes depending on the combination of the in-plane and out-of-plane behaviour. Therefore, the contribution of IM panels should be considered in the structural response analysis of existing buildings, for which an understanding of the out-of-plane non-linear behaviour of IM walls is of paramount importance in order to develop efficient strengthening solutions to prevent collapse and improve their performance in future earthquakes, and consequently reduce their seismic vulnerability. In order to obtain further knowledge of the out-of-plane response of IM panels, a study of full-scale IM walls was carried out with the realization of three experimental (cyclic and monotonic) out-of-plane tests with and without previous in-plane damage. The experiments, material characterization and the test set-up will be described in this paper as well as presenting and discussing the main test results, namely in terms of hysteretic force-displacement curves, damage evolution, stiffness degradation and energy dissipation.